Plato and the (Timely) Untimeliness of Normative Utopia: A Profile of Mario Vegetti - Ferrari, Franco (Revista Archai, 2018)
Plato and the (Timely) Untimeliness of Normative Utopia. A Profile of Mario Vegetti.